Antisialogogue Effect of Atropine Sulfate at Dosages of 0.25 Mg and 0.5 Mg Under General Anesthesia with Ketamin - Hasibuan, Muhammad Ramadhan; Lubis, Andriamuri Primaputra; Wijaya, Dadik Wahyu (Journal of Society Medicine, 2022)
Introduction: Excessive saliva production can becomes an airway problem in conditions of decreased consciousness where there is impaired swallowing function. It increases the risk of aspiration of saliva into the airways that can result in choking. The use of premedication drugs to reduce the incidence of drug-induced hypersalivation can be done as a prevention. The anticholinergic drug class is the drug of choice for the management of hypersalivation in general anesthesia patients who have been given ketamine and ether. Ketamine as a sedating agent will provide a side effect of hypersalivation, where hypersalivation can cause laryngospasm or aspiration, as a form of prevention, anticholinergic drugs such as atropine can be given. The aim of this research was to compare the effect of antisialagogue on the administration of atropine sulfate at a dose of 0.25 mg and 0.5 mg in intravenous general anesthesia patients without ETT with ketamine at Haji Adam Malik General Hospital Medan and Putri Hijau Hospital Medan. Method: This study used a double blind RCT design. A total of 60 patients with intravenous general anesthesia without ETT with ketamine (1-2 mg/kg BW) were divided into 2 groups of Atropine Sulfas doses (0.25 and 0.5 mg) then the total salivary volume of each patient was measured and analyzed. Results: There was a significant difference between the treatment groups of 0.25 mg and 0.5 mg in the volume of saliva that had been collected (P-value = 0.008). Conclusion: There was a significant comparison between the use of 0.25 mg and 0.5 mg atropine in patients at Haji Adam Malik Hospital and Putri Hijau Hospital Medan.